2018
DOI: 10.2147/ijn.s159327
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, in vitro and in vivo anti-tumor effect of thalidomide nanoparticles on lung cancer

Abstract: IntroductionThalidomide (THA) is an angiogenesis inhibitor and an efficient inhibitor of the tumor necrosis factor-α (TNF-α). However, the clinical application of THA has been limited due to hydrophobicity of the compound.Materials and methodsTo increase the water solubility of THA and in order to evaluate the anticancer abilities of this material on human lung carcinoma, methoxy poly(ethylene glycol)-poly(ε-caprolactone) nanoparticles loaded with THA (THA-NPs) were prepared. The synthesis of THA-NPs was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Recently, nanoparticles have attracted increasing attention for the dramatic enhanced anticancer effects and reduced systemic toxicity in chemotherapy. 16 It has been reported that encapsulation of anticancer drugs by nanoparticles could efficiently deliver drugs to tumor sites through an EPR effect and superior pharmacokinetics profiles in vivo, resulting in prolonged drug circulation and reduced systemic toxicity in vivo. 17 MPEG-PLA nanoparticles show high EE, stability and low clearance, which make it as a promising delivery tool for chemotherapeutic drugs.…”
Section: Mpeg-pla Nanoparticles Encapsulated Cq-and Dox-induced Enhanmentioning
confidence: 99%
“…Recently, nanoparticles have attracted increasing attention for the dramatic enhanced anticancer effects and reduced systemic toxicity in chemotherapy. 16 It has been reported that encapsulation of anticancer drugs by nanoparticles could efficiently deliver drugs to tumor sites through an EPR effect and superior pharmacokinetics profiles in vivo, resulting in prolonged drug circulation and reduced systemic toxicity in vivo. 17 MPEG-PLA nanoparticles show high EE, stability and low clearance, which make it as a promising delivery tool for chemotherapeutic drugs.…”
Section: Mpeg-pla Nanoparticles Encapsulated Cq-and Dox-induced Enhanmentioning
confidence: 99%
“…Additionally, CQ, with proven efficiency in preclinical studies, has been reported to present difficulties in passing through the cell membrane in the presence of acidic extracellular microenvironments, which is characteristic of tumors [ 9 , 11 ]. This problem could be overcome by the encapsulation of CQ using nanoparticles, an approach that has been demonstrated to increase not only the CQ antitumor effect but also the efficient delivery of drugs to tumor sites with superior pharmacokinetic profiles, prolonged drug circulation, and reduced systemic toxicity in vivo [ 15 , 16 , 82 , 83 , 84 ]. The encapsulation of CQ together with an NHEJ inhibitor could then be explored for the treatment of OC to recapitulate the efficacy of this combination shown in this work.…”
Section: Discussionmentioning
confidence: 99%
“…This information could be of paramount importance in clinical settings. Food intake delayed (T max ) but increased TAL absorption (C max and AUC), in line with the negligible hydrophilicity of the active compound [ 30 31 ]. Interestingly, the effect of food on TAL pharmacokinetics in humans are conflicting: some studies report no influences while others report minor effects on C max and AUC, with a significant delay to T max [ 2 28 ].…”
Section: Discussionmentioning
confidence: 99%